2016
DOI: 10.3389/fphys.2016.00180
|View full text |Cite
|
Sign up to set email alerts
|

Pelleted Bone Marrow Derived Mesenchymal Stem Cells Are Better Protected from the Deleterious Effects of Arthroscopic Heat Shock

Abstract: Introduction: The impact of arthroscopic temperature on joint tissues is poorly understood and it is not known how mesenchymal stem cells (MSCs) respond to the effects of heat generated by the device during the process of arthroscopy assisted experimental cell-based therapy. In the present study, we isolated and phenotypically characterized human bone marrow mesenchymal stem cells (hBMMSCs) from osteoarthritis (OA) patients, and evaluated the effect of arthroscopic heat on cells in suspension and pellet cultur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 42 publications
1
14
0
Order By: Relevance
“…Unlike the MSCs isolated from adult tissues, the hWJSCs being relative young phenotype showed active cell proliferation with time. This was supported by earlier studies, which identified the doubling time of these hWJSCs to be much shorter [ 10 , 11 ], thus it can support generation of sufficient cell numbers needed for regenerative medicine applications.…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…Unlike the MSCs isolated from adult tissues, the hWJSCs being relative young phenotype showed active cell proliferation with time. This was supported by earlier studies, which identified the doubling time of these hWJSCs to be much shorter [ 10 , 11 ], thus it can support generation of sufficient cell numbers needed for regenerative medicine applications.…”
Section: Discussionsupporting
confidence: 61%
“…Derived cells were analysed for the presence of MSC related CD surface markers expression using fluorescent activated cell sorting (FACS) analysis as reported earlier [ 11 ]. Briefly, independent aliquots of cells (2 x 105) were treated with MSC isotype/phenotype cocktails (Miltenyi Biotec) or combination of individual antibodies (CD29, CD44; BD Pharmingen) to avoid interference of fluorochromes.…”
Section: Methodsmentioning
confidence: 99%
“…Kalamegam et al Mentioned that the repair of articular cartilage injury by several methods were functionally inadequate in the long term and increased the risk of further damage [14]. Based on these reasons, the repair methods of damaged articular cartilage are limited and the traditional treatments are not ideal.…”
Section: Discussionmentioning
confidence: 99%
“…BM-MSCs related CD markers expression was analyzed from cells of early passages (P1-P3) using FACS analysis as reported earlier (Kalamegam et al, 2016). Briefly, the cells were trypsinized upon reaching 70% confluence, using 0.25% Trypsin-EDTA (Life Technologies, Thermo Fisher Scientific, Waltham, MA, United States), centrifuged at 500 g × 5 min.…”
Section: Flow Cytometry Analysis Of CD Markersmentioning
confidence: 99%